SYSMAS: a handy software to manage by SMS & Web interface notifications on HWC & other wildlife events… - Le Bel, Sébastien, speaker; Chavernac, David, speaker; Breck, Stewart, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Human-wildlife conflicts have drastically increased around conservation areas in Africa in recent decades, thus undermining the peaceful cohabitation of wildlife populations and rural human settlements. Mitigation packages include various reporting forms, which are often ineffective since the information conveyed is generally scattered and useless. The booming mobile phone sector and the popular use of text messages (SMS) have provided an opportunity to assess the impact of real-time communication systems in human-wildlife conflict mitigation strategies. After preliminary tests conducted in Mozambique and Zimbabwe with FrontlineSMS, we improved the recording and transfer of raw information generated at field level with the development of an integrated system called SYSMAS. Apart from improving the quality of wildlife based information, SYSMAS was developed as a handy management tool informing in real time decision makers and easy to upload even without specific computer skills. This paper details how easy any human-wildlife conflict incident or wildlife event can be translated into a set of explanatory variables and captured on mobile phones with ad-hoc SMS models. According to local communication facilities, real-time sharing of the information could be achieved directly through a Web interface or via SMS; this last been more handy in remote African farmland. Once adopted, such a human-wildlife conflict early warning system could be deployed at low cost. The same approach could be promoted for the establishment of reporting systems on wildlife disease outbreaks.
SYSMAS: a handy software to manage by SMS and Web interface notifications on human and wildlife conflicts and other wildlife related events
Moderator: Stewart Breck.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Video presenter: Sébastien Le Bel.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses